2019
DOI: 10.1016/j.ijbiomac.2018.12.099
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a native group III trypsin ZT from Atlantic cod (Gadus morhua)

Abstract: Atlantic cod trypsin ZT is biochemically characterized for the first time in this report in comparison to a group I trypsin (cod trypsin I). To our knowledge, trypsin ZT is the first thoroughly characterized group III trypsin. A more detailed understanding of trypsin ZT biochemistry may give insight into its physiological role as well as its potential use within the biotechnology sector. Stability is an important factor when it comes to practical applications of enzymes. Compared to trypsin I, trypsin ZT shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Moreover, while most studies on digestive biochemistry of fish have reported several isoenzymes for different enzymes, only a handful of studies have investigated the adaptive value of this isoenzyme richness. The occurrence of multiple isoforms for digestive proteases is thought to provide an adaptive advantage for insects feeding on plants containing inhibitors (Dıáz-Mendoza et al, 2005), for crustaceans feeding on a broad diet (Saborowski et al, 2012;Perera et al, 2015), and as an adaptation to environmental temperature in only few fish species (Gelman et al, 2008;Sandholt et al, 2019). In the Atlantic salmon (Salmo salar), trypsin isoenzymes have been thoroughly studied (Torrissen, 1987;Rungruangsak-Torrissen, 2012) and related to differences in the absorption and transport of free amino acids (Torrissen et al, 1994;Rungruangsak-Torrissen and Male, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while most studies on digestive biochemistry of fish have reported several isoenzymes for different enzymes, only a handful of studies have investigated the adaptive value of this isoenzyme richness. The occurrence of multiple isoforms for digestive proteases is thought to provide an adaptive advantage for insects feeding on plants containing inhibitors (Dıáz-Mendoza et al, 2005), for crustaceans feeding on a broad diet (Saborowski et al, 2012;Perera et al, 2015), and as an adaptation to environmental temperature in only few fish species (Gelman et al, 2008;Sandholt et al, 2019). In the Atlantic salmon (Salmo salar), trypsin isoenzymes have been thoroughly studied (Torrissen, 1987;Rungruangsak-Torrissen, 2012) and related to differences in the absorption and transport of free amino acids (Torrissen et al, 1994;Rungruangsak-Torrissen and Male, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The spike protein S is responsible for the entry of coronaviruses into host cells 3 . Trypsin cleaves at arginine and lysine amino acid residues within proteins 5 . There are over 100 lysine and arginine residues present within SARS‐CoV‐2 S protein (GenBank QHD43416.1) and about 80 such residues in HCoV‐229E S protein (GenBank ABB90529.1).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results presented in this study, CZ-MD was found to inactivate SARS-CoV-2 (98.3%) and HCoV-229E (99.9%) in vitro (Table 1) Trypsin cleaves at arginine and lysine amino acid residues within proteins. 5 There are over 100 lysine and arginine residues present within SARS-CoV-2 S protein (GenBank QHD43416.1) and about 80 such residues in HCoV-229E S protein (GenBank ABB90529.1). These trypsin specific sites within the S proteins of SARS-CoV-2 and HCoV-229E may not be readily accessible due to a glycan shield and some of the lysine or arginine residues may be buried within the S protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ColdZyme is a class III medical device (CE-marked) composed of glycerol, water, buffer, CaCl 2 , menthol, and trypsin from the Atlantic cod ( Gadus morhua ) ( 6 ) (ClinicalTrials.gov, ID: NCT03901846). The ColdZyme mouth spray forms a physical barrier that interferes with entry of common cold viruses, which subsequently become trapped and inactivated ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%